(untitled) (Contemporary Journal of Social Science Review, 2025)
This study investigates the mystery of happiness disparity between Pakistan and India in spite of India’s strong economy. The study uses inequality regression models to identify key variables, such as age, gender, education, and geopolitical issues, that contribute to the happiness gap between the two nations. While the unexplained effect suggests elusive forces, the explained effect predominates, highlighting the significance of quantifiable elements. The results highlight the necessity of all-encompassing policies that address both material and immaterial factors in order to promote overall well-being in both countries.